Napovedniki zadovoljstva v partnerskem odnosu pri moških in ženskah - Zager Kocjan, Gaja (Psihološka obzorja (Ljubljana), 2014)
The present study was designed to examine the differences between genders in the perception of romantic relationship as well as in aspects of the relationship that are important for their relationship satisfaction. However, previous studies rarely report significant differences between genders in various predictors of the relationship satisfaction. In our study, similar conclusions were obtained. Relationship satisfaction was predicted with attachment, self-esteem, and partner's social support. The study included 200 participants (63.5% of women) who completed the following questionnaires: Experience in Close Relationships - Revised Short ECR-RS, Quality of Relationship Inventory QRI, Relationship Satisfaction Scale RSS, and a single-item self-esteem measure. For both genders, significant positive predictor of their relationship satisfaction was self-esteem, while avoidance, anxiety, and conflict in the relationship were significant negative predictors. There were no significant differences between genders. These findings are consistent with the findings of previous studies, which rarely report significant gender differences in the various predictors
Keywords: partnerski odnos; relationship satisfaction; gender differences; zadovoljstvo; razlike med spoloma; self-esteem; social support; samospoštovanje; socialna opora; attachment; attachment theory; navezanost; Quality of relationship inventory; Relationship satisfaction survey; Vprašalnik kvalitete odnosa QR; Vprašalnik zadovoljstva s partnerskim odnosom